KINERJA PEGAWAI DITINJAU DARI PENGETAHUAN, PELATIHAN, KOMPETENSI DAN MOTIVASI PADA PETUGAS PEMADAM KEBAKARAN DI KABUPATEN KLATEN - Sumino Sumino; Sarsono Sarsono; Ida Aryati Diyah Purnomo Wulan (EKOBIS, 2022)
The purpose of this study or research is to prove and analyze how far the influence between variables, both simultaneously and partially, is on four variables, namely knowledge, training, competence and motivation for Firefighters in Klaten Regency, Central Java. The design of this research or research uses descriptive quantitative research methods. The research population or research is all employees who are on duty or at the Klaten Regency Fire Department, Central Java, with a total of 35 (thirty five) people. The sample used in this study was the entire population in the Fire Department in Klaten Regency, Central Java. This data collection uses data in the form of questionnaires which are distributed to all respondents in the Fire Department in Klaten Regency, Central Java. The data analysis technique used was statistical analysis, namely multiple linear regression, F test, t test, and the coefficient of determination. The results of this study indicate that the variables of knowledge, training, competence and motivation partially and significantly have a very significant effect on the performance of Firefighters in Klaten Regency, Central Java. Suggestions from this study, Firefighters in Klaten Regency are asked and expected to continue to improve the existing knowledge, training, competence and motivation so far, so that it is hoped that the performance of the employees will increase and be better than the previous office's vision and mission. Fire in Klaten Regency will be achieved. Thus, this research is expected to bring good changes in the Fire Department in Klaten Regency, Central Java for the better.